Effects of fertilizer application method on vegetative growth of Andrographis paniculata Wall ex. Ness - Zahid, Nurliyana (2015)
Demand for organic herbs is high due to health awareness and its uses for alternative medicinal treatment. Andrographis paniculata is known for its beneficial properties such as antiglychemic, antimicrobial and antioxidant. Hence this study was conducted to determine suitable methods of fertilizer application for vegetative growth production of A.paniculata. Five treatments tested in this study were, control (T0) :chicken manure 210kgN/ha fertilizer application at transplanting (AT), T1:chicken manure two times split applications (140kgN/ha AT and 70kgN/ha14 DAT), T2:chicken manure three time split applications (140kgN/ha AT, 35kgN/ha 14 DAT, 35kgN/ha 21 DAT), T3: chicken manure application 140kgN/ha (AT) combined with Biojadi foliar application (70kgN/ha 14 DAT), T4:chicken manure application 140kgN/ha (AT) combined with two time split Biojadi foliar application (35kgN/ha 14 DAT and 35kgN/ha 21 DAT). Equivalent rate of 210kgN/ha was applied for all treatments. Results indicate that, there were significant differences (p<0.05) in total fresh weight, total biomass, relative chlorophyll content and phosphorus content affected by method of fertilizer application. Plant that treated with chicken manure application only at transplant produced higher yield plant biomass and relative chlorophyll content. Among all treatments, plants that were treated with chicken manure fertilizer at transplanting (100%) and combine of chicken manure (AT) with two times split foliar application produced high plant biomass and relative chlorophyll content compared to other treatments. High P content was observed in plant treated with two times split chicken manure application.Results suggested that organic fertilizer application at transplant (AT) is the suitable method for high production of vegetative part of A.paniculata.